if one root is equal to the square of the other root of the equation x square + x - k = 0 , then find k
Answers
Answered by
1
Answer: Let one root be a, other root is a^2.
Sum of the roots = a + a^2 = - b/a = -1.
So a^2 = -1-a
Product of the roots = a^3 = -k or a(-1-a) = -k.
i.e., -a-a^2 = -k or -a-(-1-a) = -k or k = - 1.
Step-by-step explanation:
Similar questions
Physics,
1 month ago
Math,
1 month ago
India Languages,
3 months ago
Psychology,
3 months ago
Math,
11 months ago
English,
11 months ago